Fear of Death in People of Mature Age with Christian Self-Identification - Anastasia A. Bakanova; Irina A. Gorkovaya (Peoples' Friendship University of Russia (RUDN University), 2022)
One of the most important functions of religion is to fill the deficits in the existence of human society, among which an important place is occupied by the awareness of human mortality. According to psychological theories, religion often appears as one of the adaptive strategies that alleviate the fear of death. However, both domestic and foreign empirical studies of the relationship between religiosity and the severity of the fear of death lead to contradictory results, which is associated with the need to take into account a large number of variables in such studies, as well as a non-linear relationship between religion and the fear of death. The authors have made an attempt to study the relationship between Christian self-identification with the conscious components of the fear of death in 118 men and women at different periods of adulthood (40-50 and 51-65 years). The conscious components of the fear of death were assessed on the Personal Death Fear Scale, and attitudes toward death (in particular, the features of experiencing the fear of death and ways to cope with it) were identified in phenomenological interviews. The data were processed using Mann - Whitney U test, correlation analysis, and phenomenological analysis of interviews. The study has shown that Christian religious self-identification in adulthood is positively correlated with the conscious fear of death, and also has age and gender specificity. In general, it is concluded that, in order to explain the relationship between Christian self-identification and the conscious fear of death, it is necessary to analyze the role that the religious worldview plays in people's understanding of their life path. Based on the results of the study, it can be assumed that the leading motive in choosing a Christian worldview is not so much overcoming the fear of personal death as the search for effective ways to cope with difficult life situations. That is why Christian self-identification does not contribute to reducing the fear of personal death, responding to a greater extent to other motives related to the need to "cope with life." To sum up, the authors show that religiosity is not a universal tool that can unequivocally reduce the fear of death.